A study on the fiber distribution characteristics of hybrid fiber reinforced high strength concrete with steel and glass fibers. (2021) - Prathipati, S.R.R. Teja; Khan, Inamullah; Rao, C.B.K.; Kasagani, Hanuma
Abstract: High strength concrete (HSC) blended with fibers will enhance the ductility of the structure, thereby making it a feasible solution in large infrastructure projects. The number of fibers bridging the cracks, and their orientation in the fracture plane will affect the mechanical behaviour and therefore assessment of fiber distribution characteristics is crucial in the calculation of mechanical properties of Fiber Reinforced High Strength Concrete (FR-HSC). In this study an experimental investigation using image analysis was carried out to ascertain the Fiber distribution characteristics (Fiber dispersion coefficient and Fiber orientation factor) of the M70 grade Mono Glass Fiber Reinforced High Strength Concrete (MGFR-HSC), Mono Steel Fiber Reinforced High Strength Concrete (MSFR-HSC), Graded Fiber Reinforced High Strength Concrete (GrFR-HSC), Hybrid Fiber Reinforced High Strength Concrete (HyFR-HSC) and Hybrid Graded Fiber Reinforced High Strength Concrete (HyGrFR-HSC). The effects of fiber distribution characteristics are quantified based on the fiber type, fiber volume, fiber length, and grading of the fibers. From the results it can be observed that graded fibers (steel/glass) specimens have exhibited higher distribution characteristics than specimens with mono fibers. Among HyGrFR-HSC and HyFR-HSC mixes, better fiber distribution characteristics was noticed in HyGrFR-HSC specimens, and this may be attributed towards better fiber dispersion without clumping in HyGrFR-HSC mixes. From this investigation, it can be concluded that the mixing of glass and steel fibers of different lengths into the concrete has shown a considerable improvement in the fiber distribution characteristics.